2022
DOI: 10.3389/fpls.2022.825492
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nitrogen Supply With High Frequency and Ramet Damage Increases the Benefits of Clonal Integration in Invasive Hydrocotyle vulgaris

Abstract: Nitrogen (N) deposition significantly affects the growth and the function of invasive clonal plants. However, the effects of heterogeneous N supply with different frequencies on the growth and the potential contribution of clonal integration in invasion plants are still unclear, especially in the complex environment considering ramet damage. To address this question, apical and basal ramets of the clonal invader Hydrocotyle vulgaris were connected or disconnected, N was added to the basal ramets with a high fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…In heterogeneous habitats, they tend to produce more shoots, ramets, and roots in high-nutrient microsites to search for high-quality patches. This enhanced clonal plant performance, measured by growth parameters, has been consistently observed in studies exploring the effects of soil nutrient heterogeneity ( de Kroon, 2007 ; de Kroon et al., 2009 ; Sun et al., 2022 ). Previous research has also reported positive effects of soil nutrient heterogeneity on some individual plants ( Wijesinghe and Handel, 1994 ; Roiloa and Retuerto, 2006 ; Bauerle et al., 2008 ; Peng et al., 2013 ) as well as plant populations ( Day et al., 2003a ; Xue et al., 2016 ).…”
Section: Introductionsupporting
confidence: 62%
“…In heterogeneous habitats, they tend to produce more shoots, ramets, and roots in high-nutrient microsites to search for high-quality patches. This enhanced clonal plant performance, measured by growth parameters, has been consistently observed in studies exploring the effects of soil nutrient heterogeneity ( de Kroon, 2007 ; de Kroon et al., 2009 ; Sun et al., 2022 ). Previous research has also reported positive effects of soil nutrient heterogeneity on some individual plants ( Wijesinghe and Handel, 1994 ; Roiloa and Retuerto, 2006 ; Bauerle et al., 2008 ; Peng et al., 2013 ) as well as plant populations ( Day et al., 2003a ; Xue et al., 2016 ).…”
Section: Introductionsupporting
confidence: 62%
“…Physiological traits such as photosynthetic pigments, antioxidant enzymes, and soluble sugars have often been implicated in survival and ecological strategies in plants under different conditions ( Mao et al., 2017 ). Plants, especially invasive plants, in different N-level environments exhibit various physiological and morphological responses ( Wan et al., 2019 ; Huang et al., 2022 ; Sun et al., 2022 ). The increased N supply environment can induce a significant effect on resource use in plants ( Wang et al., 2017 ; Wan et al., 2019 ); therefore, continuous N addition conditions will promote plant invasion ( Liu et al., 2018a ; Luo et al., 2020 ), such as facilitating invasive plants to synthesize more photosynthetic compounds in the leaves, which supports plant growth ( Huang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of physiological integration can be seen with respect to resource acquisition and translocation [103,104] and it also gives an ability to avoid patches of grass [105] as well as promotes resilience to grazing Physiological and ecological aspects of clonal integration in H. vulgaris have been extensively studied, recently mostly in conjunction with the high potential invasiveness of the species in China. A very high level of clonal integration seems to be associated with the expressed invasive character of the species, especially benefiting in conditions of heterogeneous water supply [93] and nutrient heterogeneity [94,95], as well as for increasing intraspecific competitiveness [96]. Although, it was not possible to experimentally prove the hypothesis that the invasiveness of H. vulgaris is directly related to the phenotypic plasticity of its individuals, as the results were inconsistent [97].…”
Section: Hydrocotyle Sppmentioning
confidence: 99%